The Effect Of Business Risk And Firm Size On Return On Assets With Capital Structure As A Moderating Variable In General Insurance Companies For The 2021-2023 Period - Annisa, Devi; Jumady, Edy; Fajriah, Yana (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to analyze the effect of business risk and firm size on profitability (ROA), with capital structure as a moderating variable in general insurance companies listed on the IDX for the 2021–2023 period. The method used is panel data regression with the Random Effect Model (REM), based on secondary data from financial statements. The results show that business risk has a significant positive effect on ROA, while firm size has no significant effect. Capital structure moderates the effect of business risk on ROA, but not firm size. These findings underline the importance of risk and capital structure management.